PEMETAAN KAWASAN TERLAYANI INFRASTRUKTUR BANGUNAN PASAR KOTA BATAM - Suci Dayanti Natali; Siti Noor Chayati, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The uneven distribution of markets makes it difficult for some areas to access market infrastructure, especially if the area has a high population density. So it is necessary to map areas that can be served by Batam City's building infrastructure using a Geographic Information System (GIS) approach. This research aims to determine the distribution pattern, density and areas served by market building infrastructure both based on distance and travel time, and find out which settlements can be reached. The results of this research have a clustered distribution pattern and density values ranging from 0–1.04, while the areas served by Batam City market infrastructure based on distance and time can reach several sub-district areas well, but Bulang and Galang sub-districts are not served because there are no the market in the district. Residential areas that can be served cover many settlements except Bulang District because there are no markets and the road network to get to markets in other districts is inadequate.